2023
DOI: 10.1111/epi.17630
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic spasms in CDKL5 deficiency disorder: Delayed treatment and poor response to first‐line therapies

Abstract: Objective: We aimed to assess the treatment response of infantile-onset epileptic spasms (ES) in CDKL5 deficiency disorder (CDD) vs other etiologies. Methods:We evaluated patients with ES from the CDKL5 Centers of Excellence and the National Infantile Spasms Consortium (NISC), with onset from 2 months to 2 years, treated with adrenocorticotropic hormone (ACTH), oral corticosteroids, vigabatrin, and/or the ketogenic diet. We excluded children with tuberous sclerosis complex, trisomy 21, or unknown etiology with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…For example, 88% of individuals with epileptic spasms due to CDKL5 deficiency were reported to have seizures prior to the onset of epileptic spasms. 16 Second, we did not find associations between any ASM and an increase or decrease in the risk for epileptic spasms. Compared to previous studies analyzing epileptic spasms in a broader cohort, we did not find that sodium channel blockers provoke epileptic spasms.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…For example, 88% of individuals with epileptic spasms due to CDKL5 deficiency were reported to have seizures prior to the onset of epileptic spasms. 16 Second, we did not find associations between any ASM and an increase or decrease in the risk for epileptic spasms. Compared to previous studies analyzing epileptic spasms in a broader cohort, we did not find that sodium channel blockers provoke epileptic spasms.…”
Section: Discussioncontrasting
confidence: 61%
“…17,18 However, in other genetic etiologies, individuals with epileptic spasms also responded poorly to standard treatment of epileptic spasms; individuals with CDKL5 deficiency have been reported to have refractory epileptic spasms in 96% compared to 53% of individuals by the National Infantile Spasms Consortium. 16 We found that individuals with prior seizures in the first few months of life as well as individuals with a later onset of epileptic spasms were more likely to develop refractory epileptic spasms. The duration of spasms was increased in individuals with previous seizures, indicating a higher seizure burden and more overall severe disease presentation compared to individuals with spasms as the first seizure type.…”
Section: Discussionmentioning
confidence: 62%
“…A recent investigation of epileptic spasms, which compared data from the same source as the study by Daniels et al 4 . (CDKL5 Centers of Excellence) with that of the National Infantile Spasms Consortium, confirmed and expanded on their characteristics in CDD 5 . These included the relatively lower association with hypsarrhythmia at their onset, prolonged lead time to treatment, and poor response to first‐line treatments 5 .…”
mentioning
confidence: 87%
“…(CDKL5 Centers of Excellence) with that of the National Infantile Spasms Consortium, confirmed and expanded on their characteristics in CDD 5 . These included the relatively lower association with hypsarrhythmia at their onset, prolonged lead time to treatment, and poor response to first‐line treatments 5 . The role of late recognition of epileptic spasms in their poor prognosis in CDD is still unclear.…”
mentioning
confidence: 95%
“…However, reports of EEGs performed during the initial stages of the disease indicates a diverse spectrum of findings, ranging from mild abnormalities to hypsarrhythmia [17]. Among cohorts of CDD patients with epileptic spasms (the most common seizure type), hypsarrhythmia was observed in only 34% of cases according to study conducted by Olson et al (2023) [18]. This factor likely contributes to a longer lead time for initiating first-line treatment for epileptic spasms in CDD.…”
Section: Epilepsy In Cdkl5 Disordermentioning
confidence: 99%